The Process of Structural Changes & Industrialization with Reference to The Italian South/عملية التغيرات الهيكلية والتصنيع مع الإشارة إلى الجنوب الإيطالى - OMAR MAHMOUD, MAHMOUD; M. Mongy.. (INP, 2024)
This study covers several key chapters, starting with the introduction, which provides an overview of the topic. Chapter I discusses economic development and structural change, highlighting their impact on the economy. Chapter II focuses on industrialization and economic development, analyzing the role of industry in promoting economic growth. Chapter III examines the occupation structure of Southern Italy, emphasizing the distribution of jobs and professions in the region. Chapter IV discusses the role of large-scale industries in Southern Italy and their contribution to economic development.